STUDI KARAKTERISASI DAERAH RAWAN LONGSOR DI DESA MALIWOWO KECAMATAN ANGKONA KABUPATEN LUWU TIMUR BERDASARKAN UJI X-RAY DIFFRACTION (XRD) - Nurlaela, Nurlaela; Said L, Muh.; Iswadi, Iswadi (Universitas Islam Negeri Alauddin Makassar, 2018)
Research has been conducted in Maliwowo village, Angkona sub-district, East Luwu district, which aims to determine the mineral content and crystal structure of the soil in Maliwowo village, Angkona sub-district, East Luwu district. The method used in this study is the sampling technique carried out with five different points with a depth of 90 cm each. The results of X-Ray Diffraction (XRD) analysis showed that the minerals contained in sample A were 54,5% ,ite kaolinite 24,2% and 21,3% merrilite with successive crystal structures, namely monoclinic, triclinic and trigonal. The sample point B is illite 43,7%, albite 39,8% and merillite 16,5% with successive monoclinic, triclinic and trigonal crystal structures. The sample point C illite 47,9%, kaolinite 28,6% and feldspar 23,5% with crystal structures mononlinic, triclinc and monoclinic respectively. The point D sample was 53.7% ,ite albite 33.9% and 12.4% feldspar with monoclinic, triclinic and monoclinic crystal structures. The sample point E illite 54.4%, feldspar 27.7% and merrilite 17.9% with successive crystalline structures namely monoclinic, triclinic and trigonal.